2012
DOI: 10.1590/s1516-35982012000600031
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of silage of maize hybrids

Abstract: -The objective of this research was to identify the potential of maize hybrids for the production of silage.Hybrids 1671B, 2B433, 20A78, SHS4070, BX1280 and DKB390 were tested in a randomized block design with three replications. The hybrids yields were evaluated (average plant height, height of ear insertion, number of broken and lodged plants/ha, leaf:stem and ear:plant ratio and production of of DM, CP and TDN/ha). There was no difference between hybrids for the variables studied, except for the height of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
1
0
4
Order By: Relevance
“…Os teores de PB encontrados por Pereira et al (2007) ficaram entre 6,19 e 6,90 no material no momento da ensilagem e foram inferiores aos obtidos na presente pesquisa (8,22%), conforme apresentados na Tabela 3. Araújo et al (2012) não observaram diferença significativa para os teores de PB (7,95%) em silagem de vários híbridos de milho.…”
Section: Híbridosunclassified
See 3 more Smart Citations
“…Os teores de PB encontrados por Pereira et al (2007) ficaram entre 6,19 e 6,90 no material no momento da ensilagem e foram inferiores aos obtidos na presente pesquisa (8,22%), conforme apresentados na Tabela 3. Araújo et al (2012) não observaram diferença significativa para os teores de PB (7,95%) em silagem de vários híbridos de milho.…”
Section: Híbridosunclassified
“…Os teores de MS não foram influenciados (P>0,05) pela altura de corte das plantas para silagem, portanto, as duas alturas podem ser utilizadas para corte de híbridos de milho destinados à produção de silagem. Da mesma forma, as alturas da planta e da espiga não exerceram influência na MS. Araújo et al (2012) avaliaram a silagem de seis híbridos de milho e verificaram que não ocorreu diferença significativa de MS entre os híbridos, cujos teores variaram de 28,8 a 34,5%, valores considerados adequados para melhor compactação e conservação da silagem.…”
Section: Híbridosunclassified
See 2 more Smart Citations
“…The Volumax genotype had higher averages for crude protein and total digestible nutrients, and the biomass genotype 201813B had the highest average for neutral detergent fiber, neutral detergent fiber corrected for ash and proteins, in vitro dry matter digestibility and in vitro NDF digestibility. According to Araújo et al (2012), who obtained contents of 28.8 to 34.5% dry matter in silages of six sorghum genotypes, which are values considered adequate for better compaction and silage preservation. Kaplan et al (2017), with 41 sorghum genotypes, found crude protein content between 3.44 and 7.03%.…”
Section: Resultsmentioning
confidence: 99%